IMPLEMENTASI ASAS DROIT DE PREFERENCE TERHADAP JAMINAN HAK TANGGUNGAN OLEH PIHAK PERBANKAN DALAM PERJANJIAN KREDIT - Lila Kurniawati Khisni; Lathifah Hanim (Jurnal Akta, 2017)
This study entitled Implementation of the principle of droit de preference to the guarantee of mortgage rights by the banks in the credit agreement. This study discusses the implementation of the principle of droit de preference on the guarantee of mortgage rights by the banks in credit agreements, the constraints found in the implementation of the principle of droit de preference on the guarantee of mortgage rights by the banks in credit agreements and how to overcome these obstacles.Implementation of the principle of droit de preference on the guarantee of mortgage by PT Bank Tabungan Pensiunan Nasional, Tbk in credit agreement Number 122 Credit Agreement in which to guarantee payment of all amount owed and obliged to be paid by debtor to bank either arising based on credit agreement and or Any change / renewal / renewal thereof then the debtor hereby deposits to the bank the guarantees which the transfer of ownership rights is evidenced by documents and agreements made in the form, amount and content satisfying the bank in the form of four plots of land. Constraints in the implementation of the principle of droit de preference on the guarantee of mortgage rights by the banks in the credit agreement include the difficulty of banks to conduct surveys on collateral pledged by debtors, difficulties in assessing the price of land and buildings by the bank other than that the debtor's academic ability in Understand all the contents of the agreement so that only give confidence to the bank to complete all the documentation related to the credit agreement process. The solution to overcome these obstacles is that the Bank checks to the Land Affairs Office because that is where the completeness of land documents, and the bank conducts field surveys after the credit agreement is implemented and by looking at the Land and Building Tax Payment Letters as the Value of Tax Objects and provide detailed explanation and Detailed on each article of the credit agreement so that the debtor will understand and understand each article of the credit agreement to be signed.Keywords: Droit de Preference Principle, Guarantee of Deposit Rights